Perancangan dan Implementasi Sistem Informasi Penjualan pada CV. Cihanjuang Inti Teknik - Badie Uddin; Dedy Suryadi; Siti Maesaroh (LPPM STT Terpadu Nurul Fikri, 2020)
The aim of the study is to analyze, design, and implement the information system of sales at CV. Cihanjuang Inti Teknik. The research method which is used in this study is design research with research, including observation, library research, documentation, and questionnaires. Microsoft Visual Basic.NET is used to make this information system and MySQL as database. The information system of sales can solve the problem of CV. Cihanjuang Inti Teknik information system. The certain access is provided by login facilities, which will show particular main menu that is correspond with the authority of office owned by the user. In the data process, the user only enter the data to the information system and system will be process the data to be a information such as sales reports, reports of goods sold, reports customer receivables and accounts receivable aging report. Sales report available in periodic report according to user needs.